A PRELIMINARY INVESTIGATION OF THE SHODHANA (DETOXIFICATION) OF ROOTS OF PLUMBAGO INDICA L. IN AYURVEDA - C, *Padumadasa; A M, Abeysekera; S D K, Meedin (International Journal of Ayurveda and Pharma Research, 2016)
Plumbago indica L. (Plumbaginaceae) is a medicinal herb, credited with a number of therapeutic properties. It is widely used in Sri Lankan traditional medicine and in Ayurveda. In Sri Lanka, Ayurveda formulations which incorporate the roots of P. indica L. are prepared using commercially available air dried material after subjecting it to a detoxification with limewater prepared from commercially available milk of lime. The detoxification process is referred to as â€œShodhanaâ€. According to the Ayurveda, this process is done to remove toxicity associated with the roots and, it can be surmised that it is done to remove toxicity associated with plumbagin, the predominant toxic naphthoquinone in P. indica L.. Shodhana of roots results in a deep maroon coloured extract arising from the calcium salt of plumbagin. Here, we report a qualitative and quantitative study of the Shodhana of roots of P. indica L. using Ultra Violet-Visible spectrophotometric and chromatographic methods to give a scientific basis for this process. A method for the quantitative extraction of plumbagin from root samples was optimized. A calibration curve for plumbagin in hexane was developed using the absorption values at 258 nm. The plumbagin content of 8.7 ± 0.1 mg/g in a fresh root sample was lowered by 19.4% to 7.0 ± 0.1 mg/g upon subjecting to Shodhana. It was found that a commercial dried root sample of P. indica L. root contained a much lower level (0.55 ± 0.05 mg/g) of plumbagin. To better understand the changes in the level of plumbagin in roots of P. indica L. during drying, a study was carried out by drying the root samples for five weeks subjecting them to analysis periodically by TLC and Ultra Violet-Visible spectrophotometric methods. The amount of plumbagin (8.6 ± 0.1 mg/g) present in fresh untreated roots at the beginning of the study was reduced by 62.7% to 3.2 ± 0.1 mg/g after one week. There was no measurable change in the plumbagin level thereafter up to week 5. The amount of plumbagin in dried roots can be further reduced by Shodhana. The total reduction of plumbagin by drying and Shodhana was 87.7%. Our results show that Shodhana of the fresh undried roots does not reduce the plumbagin content substantially, and that air drying followed by Shodhana is the most effective method to reduce the plumbagin content to a non-toxic level, supporting the currently used processing method.